Effect of psychosocial interventions on the severity of premenstrual syndrome: a meta-analysis - Jeehee Han; Yerin Cha; Sue Kim (Taylor & Francis Group, 2019)
Introduction: Premenstrual syndrome (PMS) is common in women with reproductive age and it affects the normal life. Psychosocial interventions are recommended for some women who experience less severe PMS. So far, no meta-analyses have investigated the effect of overall psychosocial interventions on the severity of PMS as an outcome. This review aims to explore the effectiveness of psychosocial intervention for PMS. Methods: We performed a systematic literature search in PubMED, CINAHL, EMbase and PsycINFO in December 2016, following methodological guidelines outlined in the literature (www.york.ac.uk/crd/ guidance). The primary outcome was the severity of PMS. Data were pooled using a random-effects meta-analysis model. Results: Pooled effects of 11 psychosocial interventions (n = 324) showed statistically significant beneficial effects on the severity of PMS (SMD -0.29, 95% CI -0.45 to -0.13, I2 = 27%). Participants who received coping skills training had significantly low severity of PMS than the control group (SMD -0.53, 95% CI -0.77 to -0.28, p < .001, I2 = 3%). There were no effects found for education program nor social support intervention. Discussion: Psychosocial interventions, especially coping skills training for women with PMS, were effective in reducing the severity of PMS. However, needed caution due to the small number of studies.